Crossdressing Masculino: Uma Visão Psicanalítica da Sexualidade Crossdresser - Kogut, Eliane Chermann (2006)
This dissertation investigates the sexuality of male transvestites here denominated crossdressers (cds) to differentiate them from the transvestites that prostitute themselves. It is an exploratory research. Thirty nine cds were interviewed; eight cds patients have attended psychoanalysis sessions for five years; the literature produced by crossdressing groups (magazines, books, supporter sites, dating sites and erotic sites) was researched and the author has developed familiarity with members of the Brazilian Crossdressing Club. The Freudian theory of psychosexual development and the psychopathologic concepts of Lacan and McDougall are utilized to guide the research, to which the concept of crossdresser erotism is aggregated after the analysis of the data. In the final part, the findings and hypotheses of the present research are compared to the already classical psychoanalytical hypotheses on this subject (notably Stoller´s and Lacanian followers ). The necessity of revising some of the classical hypotheses of the crossdressers psychodynamic is stressed, as well as the relationships with fetishism and with perversion. Clinical suggestions to attend crossdressers are also presented